Status of hydropower and water resources in the Southeastern Anatolia Project (GAP) of Turkey - Murat Kankal; Sinan Nacar; Ergun Uzlu (Energy Reports, 2016)
This study focuses on the water resources development of the Southeastern Anatolia Project (GAP) in Turkey. The Euphrates and Tigris Rivers, located in the GAP, have the largest flow volume of 16.9% and 11.4% of Turkey's average annually runoff (186 billion m3), respectively. While the Euphrates represents over 19.4% of the national gross hydropower potential (433 GWh/year), the Tigris correspond to 11.2% of this potential. 20,523 GWh/year of hydropower potential in the GAP is in operation. When all projects of the GAP in planning are completed, the total hydropower potential reaches a level of 27,419 GWh/year. This value corresponds to 10.9% of the annual electric energy production of Turkey in 2014 (251.96 GWh). There is also irrigable land of 1.06 million ha in the GAP, and now roughly 33.7%, 357,241 ha, of which have been irrigated.
Keywords: 330; Euphrates-Tigris Basin; Hydropower; Irrigation; Southern Anatolia Project